Coupled and decoupled responses of continental and marine organic‐sedimentary systems through the Paleocene‐Eocene thermal maximum, New Jersey margin, USA. (23rd March 2013) - Schneider‐Mor, Aya; Bowen, Gabriel J.
Abstract : [1] The flux of sediment and organic carbon from continents to the coastal ocean is an important factor governing organic burial in coastal sediments, and these systems preserve important records of environmental and biogeochemical conditions during past global change events. Burial of organic materials in coastal systems can be promoted by chemical resilience or through protection by association with mineral surfaces, but the role and influence of these processes on organic records from ancient sediments is poorly known. We studied sediment and organic matter burial as particulate organic matter (POM) and mineral‐bound organic matter (MOM) in near‐shore marine sediments from the Wilson Lake core (New Jersey, USA) that span the Paleocene‐Eocene thermal maximum (PETM), a climatic perturbation 55.9 Myr ago. Our results show that distinct POM and MOM fractions can be isolated from sediments. Both fractions appear to be dominated by terrestrial material, but POM consisted primarily of recently synthesized material whereas MOM included a significant fraction of pre‐aged organic matter from soils or ancient sediments. Variation in organic burial through the PETM is associated with changes in inorganic nitrogen burial, clay mineralogy, and clastic grain size that we associate with enhanced continental weathering, erosion and redeposition of ancient kaolinites, and eustatic sea level variation, respectively. These results provide a new perspective on factors governing carbon burial and carbon isotope records in ancient marine margin settings and offer information on rate and phasing of late Paleocene/early Eocene Earth system changes that may constrain interpretations of the cause of the PETM climate change event. Key Points: Particulate and minerals bound organic fractions have a distinct origin Combination of minerals and organic elucidate the coupled land/ocean systems Variation in organic burial associated with weathering and redeposition of clays